Risk assessment of wind generation dispatch using monte carlo simulation - Abd. El-Moneim Shaaban, Mohamed (2013)
The risk associated with introducing wind turbines into the generation fleet is investigated in this paper. The loss of load probability (LOLP) and statistical expected demand not supplied (EDNS) are adopted as the risk indices. A case study is reported to evaluate the risk posed by displacing conventional generation with wind turbines. Results on the test system show that multiples of wind turbine capacities are needed to displace conventional generation capacity to preserve the system reliability level. On the other hand, noticeable reduction is CO2 emission is achieved when wind turbines are present in the generation mix.